Deficiency of BLOS1 moderately impairs the biogenesis of platelet dense granules - Yefeng Yuan; Wei Li (Platelets)
Defects in platelet secretion contribute to hemorrhagic disorders and coagulopathies, primarily link to the biogenesis of lysosome-related organelles (LROs), namely alpha granules (AGs) and dense granules (DGs). While deficiencies in the biogenesis of lysosome-related organelles complex-1 (BLOC-1) are known to impair DG formation and platelet function, the distinct roles of individual BLOC-1 subunits remain unresolved. Here, we investigated BLOS1, a shared subunit of BLOC-1 and BLOC-1-related complex (BORC) encoded by BLOC1S1. Through comparative analysis of platelet-specific Bloc1s1-conditional knockout (Bloc1s1-cKO) mice and sdy mice (deficiency in BLOC-1 subunit dysbindin), we found that Bloc1s1-cKO platelets exhibited a 50% reduction in DG content compared to sdy mice, indicating BLOS1 deficiency causes moderate DG biogenesis defects. Consistently, agonist-induced DG secretion in Bloc1s1-cKO mice was moderately impaired relative to the severe defects in sdy mice. Distinct steady-state levels of granule proteins were observed between the two mutants. These findings suggest that dysbindin (only in BLOC-1) and BLOS1 (a shared BLOC-1 and BORC subunit) regulate LRO biogenesis and function in a different manner.